PRODUCT DEVELOPMENT AS WEECO TARTLET DIVERSIFICATION OF LOCAL FOOD PRODUCTS BASED TART - Ichda Chayati, Prillasita Ayu Kusuma (Prosiding Pendidikan Teknik Boga Busana, 2020)
Weeco tartlet tarts is a product made from wheat flour substitution with millet flour. This tart has a sweet, crunchy texture, and comes with sweet corn custard / creamy sweet corn custard. This study aims to 1) Find the right recipe for the product Weeco tartlet, 2) Know public acceptance of products Weeco tartlet, and 3) Find nutritional information contained in the product Sweet Weeco tartlet. This type of research used in this research is using R & D (research and development) with a model of development in this research is the 4D development model (define, design, develop, and disseminate). The results showed that the elected tart is tart with millet flour substitution as much as 50% because it has characteristics approaching the reference product and still be accepted by consumers. Nutrient content contained in tartlet Weeco showed levels of carbohydrates as much as 40.6661%, 5.3460% protein, fat 22.3306% 20.0585% water, ash 1.8299%, 9.7686% crude fiber, and contain as much total energy 381.4844 cal / 100gr weeco tartlet. Keywords: Wheat Millet, Tart,